Indonesian Information Extraction : Challenges and Opportunities - Yan Puspitarani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Information extraction is part of natural language processing, aiming to find, retrieve, or process information. The data source for information extraction is text. Text cannot be separated from people's daily lives. Through text, a lot of confidential information can be obtained. To produce information, the unstructured text will be converted into structured data. There are many approaches that researchers take to this process. Most of the studies are in English. Therefore, this paper will present current research trends, challenges, and information extraction opportunities using Indonesian.